FOLLISTATIN: A COMPREHENSIVE RESEARCH-BASED OVERVIEW - Amonova Gulafzal Uzbekboyevna; Remo Pal (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Follistatin is a glycoprotein that plays a pivotal role in various physiological processes by binding and neutralizing members of the transforming growth factor-beta (TGF-β) superfamily, notably activins and myostatin. This interaction influences muscle growth, inflammation, fertility, and cellular signaling pathways.The purpose of the study. Follistatin, also known as activin-bindings protein, is a protein that in humans is encoded by the FST gene. Follistatin is an autocrine glycoprotein that is expressed in nearly all tissues of higher animals.Research material and methods. Structure and Isoforms: Follistatin is primarily produced in the liver and is present in nearly all body tissues. It exists in multiple isoforms resulting from alternative splicing:• Follistatin 344 (FS-344): The most basic form, primarily used in gene therapy research. It can be converted into other forms to target different tissues.• Follistatin 315: The main form found in the bloodstream, predominantly targeting muscle tissue.• Follistatin 288: Involved mainly in reproductive health and has implications in tumor development.